2017
DOI: 10.1111/jocn.13656
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking presence: a grounded theory of nurses and teleconsultation

Abstract: Teleconsultation provides an innovative approach to enhancing the delivery of health care. This study provides nurses with insight into the impact of teleconsultation on their professional role, and an understanding of how best to use video-mediated communication to support patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 40 publications
1
68
0
1
Order By: Relevance
“…For instance, inability to understand the functions of a mobile safety alarm may result in the user failing to call for help in the case of an emergency. Studies also report that limitations associated with the technology, such as technical failure, can inhibit the uptake and adoption of the technology by nurses (Barrett, ). Moreover, if older adults repeatedly find the technology unreliable or difficult to understand, they may develop a negative attitude towards the telecare device and not bother using it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, inability to understand the functions of a mobile safety alarm may result in the user failing to call for help in the case of an emergency. Studies also report that limitations associated with the technology, such as technical failure, can inhibit the uptake and adoption of the technology by nurses (Barrett, ). Moreover, if older adults repeatedly find the technology unreliable or difficult to understand, they may develop a negative attitude towards the telecare device and not bother using it.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found that home healthcare nurses who delivered health services through virtual visits evaluated the virtual visit technology positively (Husebø & Storm, ). Moreover, in a study performed by Barrett () aimed at understanding how teleconsultation has an impact on the role of nurses, it was reported that nurses have different types of presence (operational, clinical, technical and social) during teleconsultation to support patient care. The degree of presence depends on specific characteristics of video‐mediated communication.…”
Section: Introductionmentioning
confidence: 99%
“…Suggestions for adapting some in-person rapport techniques such as the use of small talk, eye contact, and body language to facilitate trust, personal connection, and communication during videoconferencing encounters have been discussed in the popular press and clinical commentaries [1,[22][23][24]. However, few studies seem to have evaluated these modalities [25][26][27][28] or more advanced relational skills such as presence [29], conveying caring [30], empathy [31], and person-centered care [32]. Even in telepsychology, where research is more robust [33], providers remain concerned about the impact of videoconferencing on therapeutic alliance and nonverbal communication channels [16,34] and are uncertain about how best to adapt techniques.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Teleconsultation is an indication of diagnosis or choice of therapy without the physical presence of the patient and provides the use of video to facilitate real-time, remote interaction between healthcare practitioners and patients. 9 This is a remote consulting activity between physicians that allows the professional to ask for the advice to 1 or more colleagues (second opinion), based on specific training and expertise, and on medical information related the management of the patient.…”
Section: Classificationmentioning
confidence: 99%